2003
DOI: 10.1002/jmv.10558
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of the precore and the core promoter region of genotype C hepatitis B virus during lamivudine therapy

Abstract: It has been reported that spontaneous or interferon (IFN)-induced hepatitis B e (HBe) seroconversion has usually been associated with the development of a stop codon in the precore region. However, the difference between lamivudine-induced seroconversion and spontaneous or IFN-induced seroconversion is not known. The aim of this study was to investigate the correlation between the evolution of the precore and core promoter mutations and lamivudine-induced seroconversion. Forty-five patients with chronic hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Particularly, at the end of follow-up, only one patient (Case II-3) had both precore and BCP mutations. Consistently, three recent studies demonstrated that in patients receiving lamivudine for chronic hepatitis B, the presence of precore and/or BCP mutation was associated with the loss of HBeAg and the lack of such mutations was frequently associated with the reversion of HBeAg [Asahina et al, 2003;Kuwahara et al, 2004;Lin et al, 2004]. Collectively, these facts support the hypothesis that the development of transient HBeAg seroconversion and seroreversion might be due to the lack of sustained precore nucleotide 1896 and BCP dinucleotide 1762/ 1764 mutations after HBeAg seroconversion.…”
Section: Discussionmentioning
confidence: 54%
“…Particularly, at the end of follow-up, only one patient (Case II-3) had both precore and BCP mutations. Consistently, three recent studies demonstrated that in patients receiving lamivudine for chronic hepatitis B, the presence of precore and/or BCP mutation was associated with the loss of HBeAg and the lack of such mutations was frequently associated with the reversion of HBeAg [Asahina et al, 2003;Kuwahara et al, 2004;Lin et al, 2004]. Collectively, these facts support the hypothesis that the development of transient HBeAg seroconversion and seroreversion might be due to the lack of sustained precore nucleotide 1896 and BCP dinucleotide 1762/ 1764 mutations after HBeAg seroconversion.…”
Section: Discussionmentioning
confidence: 54%
“…Likewise, in HBeAg-negative patients, wild-type codon 28 preCore genomes were detected in lower percentages (0.02–0.14%), explaining cases of natural or LMV-related seroreversion (38,39). An interesting observation in the longitudinally studied patient was the significant decrease in the main preCore mutation at VBK, which coincides with reports suggesting that HBV strains carrying preCore stop codon 28 and no Pol resistant variants are more sensitive to LMV treatment than preCore wild-type sequences (35,38,39). However, additional longitudinal UDPS analyses, as reported in the present study, must be performed to further substantiate this possibility.…”
Section: Discussionmentioning
confidence: 98%
“…Insertions at the HNF1 site were observed in sequences from patients with immunosuppressive therapy (10,19,30); no therapy except IFN was included in this case. Although sequences for many patients undergoing IFN therapy have been reported (7,12,18,42), the HNF1 replacement has not been reported, as mentioned in the database research results. However, most of the database-deposited HBV genome sequences for patients with IFN therapy are genotypes HBV/A, -B, -C, and -D. There have been no reports of HBV/E-related chronic hepatitis patients who were treated with IFN therapy.…”
Section: Discussionmentioning
confidence: 99%